2018
DOI: 10.3390/w10111624
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Root Water Uptake of Surface-Irrigated Apples Using Water Stable Isotopes and the Hydrus-1D Model

Abstract: The future production of irrigated fruit orchards in the Loess Plateau of China is threatened by a shortage of freshwater. To improve water use efficiency under conditions where irrigation is limited, it is necessary to quantify the root water uptake (RWU) of apple trees. The RWU of apple trees was estimated under surface irrigation using water stable isotope technology and the Hydrus-1D model. Using the Romero-Saltos and IsoSource models, the stable isotopes of water in stems, different soil depths, and diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 46 publications
1
20
0
Order By: Relevance
“…Hydrus 1D is a well‐validated, widely used, state‐of‐the‐art soil water flow model (Šimůnek et al, ; Zheng et al, ). Model development continues, but Hydrus is essentially a soil physics model and not a physiological or plant competition model.…”
Section: Discussionmentioning
confidence: 99%
“…Hydrus 1D is a well‐validated, widely used, state‐of‐the‐art soil water flow model (Šimůnek et al, ; Zheng et al, ). Model development continues, but Hydrus is essentially a soil physics model and not a physiological or plant competition model.…”
Section: Discussionmentioning
confidence: 99%
“…Isotope studies reported different soil depths of RWU for 5-, 10-, 15-, and 22-year-old apple trees (Malus sp.) in China, with soil depths contributions varying between 10 and 300 cm, and 22-year old apple trees mainly using water from the whole soil profile down to cm during all growing stages (Wang et al, 2018;Zheng et al, 2018;. Similarly, another study carried out in China revealed that 4-year-old jujube trees mainly used soil water from 0-20 cm and 20-60 cm layers, 8-year-old trees shifted flexibly their water sources between 0-20 cm, 20-60 cm, and 60-200 cm layers, whereas 15-and 22-year-old trees often ignored moisture in shallow layers and primarily used water from the deeper soils, especially when precipitation was low (Huo et al, 2018).…”
Section: Water Sources For Plant Water Uptakementioning
confidence: 99%
“…The purpose of the water uptake modeling was to translate observed differences in tracer uptake distributions into simulated differences in the depth, time, and amount of water uptake by tree and grass roots. Following the approach of Kulmatiski et al (2020), we used Hydrus 1D, a numerical model that simulates interception, infiltration, evaporation, water flow through the soil matrix, and water uptake from a root distribution to simulate water uptake by tree and grass rooting distributions over time (Simunek, Van Genuchten, & Sejna, 2005;Zheng et al, 2018). Model simulations were first performed using a published root biomass distribution for the site (Kulmatiski et al, 2017).…”
Section: Water Uptakementioning
confidence: 99%